Assessment of the mutagenic, recombinogenic and carcinogenic potential of fipronil insecticide in somatic cells of Drosophila melanogaster. (December 2016) - de Morais, Cássio Resende; Bonetti, Ana Maria; Carvalho, Stephan Malfitano; de Rezende, Alexandre Azenha Alves; Araujo, Galber Rodrigues; Spanó, Mário Antônio
Abstract: Fipronil (FP) is an insecticide that belongs to the phenylpyrazole chemical family and is used to control pests by blocking GABA receptor at the entrance channel of the chlorine neurons. The aim of this study was to evaluate the mutagenic, recombinogenic and carcinogenic potential of FP. The mutagenic and recombinogenic effects were evaluated using the somatic mutation and recombination test (SMART) on wing cells of Drosophila melanogaster. Third instar larvae from standard (ST) and high bioactivation (HB) crosses were treated with different concentrations of FP (0.3, 0.7, 1.5 or 3.0 × 10 −5 mM). The results showed mutagenic effects at all concentrations tested in the HB cross; and all concentrations tested in the ST cross, except at concentration of 0.7 × 10 −5 mM. The carcinogenic effect of FP was assayed through the test for detection of epithelial tumor ( warts ) in D. melanogaster . Third instar larvae from wts /TM3 virgin females mated to mwh / mwh males were treated with different concentrations of FP (0.3, 0.7, 1.5 or 3.0 × 10 −5 mM). All these concentrations induced a statistically significant increase in tumor frequency. In conclusion, FP proved to be mutagenic, recombinogenic and carcinogenic in somatic cells of D. melanogaster. Highlights: The mutagenic, recombinogenic and carcinogenic potential of fipronil was studied in vivo. Fipronil has mutagenic and recombinogenic action in standard and high-bioactivation crosses. Fipronil has carcinogenic action. Increasing the metabolic capacity increases the toxic effect of fipronil.